2007
DOI: 10.1021/jp0671244
|View full text |Cite
|
Sign up to set email alerts
|

Core and Valence Band Photoemission Study of Highly Strained Ultrathin NiO Films on Pd(100)

Abstract: We discuss the results of an extensive investigation on NiO ultrathin films grown on Pd(100), carried out by means of high-resolution X-ray photoelectron spectroscopy (core levels) and ultraviolet photoelectron spectroscopy (valence band levels). The peculiarity of the investigated system is the rather high lattice mismatch between NiO and the Pd substrate (7.3%). Detailed information on the electronic structure of NiO ultrathin films is obtained as a function of thickness, with a particular emphasis put on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…The XPS region containing the Pd 3p 3/2 and O 1s peaks is rather uninformative, due to the large overlap between the two peaks. Anyway, no significant change in the band envelope as a function of the Ag coverage is observed and the peak positions are those already reported for the substrate (Pd 3p 3/2 component at 531.9 eV, O 1s component at 529.3 eV in NiO x /Pd(1 0 0)) [38]. Fig.…”
Section: Xps Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The XPS region containing the Pd 3p 3/2 and O 1s peaks is rather uninformative, due to the large overlap between the two peaks. Anyway, no significant change in the band envelope as a function of the Ag coverage is observed and the peak positions are those already reported for the substrate (Pd 3p 3/2 component at 531.9 eV, O 1s component at 529.3 eV in NiO x /Pd(1 0 0)) [38]. Fig.…”
Section: Xps Resultssupporting
confidence: 78%
“…1a reports the XPS Ni 2p. For a detailed interpretation of the Ni 2p photoemission spectrum of the c(4 · 2) phase we refer the reader to a previous publication [38]. Here it is sufficient to note that as soon as Ag is deposited, a shoulder appears at the higher BE side of the main peak, and the peak maximum progressively shifts towards higher BE while increasing the Ag dose (at 2.5 MLE DE BE = 0.8 eV).…”
Section: Xps Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…More useful in this respect is to analyze the satellite fingerprint of the photoemission lines, which, in the case of 2p transition metals is very distinctive of the oxidation state [23]. Thus by comparing the positions and relative intensities of the main photoemission peak and satellites [24][25][26][27][28] it can be concluded that all the doping ions are present predominantly as divalent cations. However the low signal to noise ratio prevents excluding the possibility of the presence of small contributions from minority oxidation states.…”
Section: Samplementioning
confidence: 99%